Pengaruh Lingkungan Belajar dan Gaya Belajar Terhadap Hasil Belajar Mahasiswa Pendidikan Matematika : The effect of learning environment and learning styles on learning outcomes in of undergraduate mathematics students - Luci Febriyanti, Yuspira; Granita (Journal of Mathematics Learning Innovation, 2025)
This study aims to analyze the influence of learning environment and learning style on the learning outcomes of Mathematics Education students at Sultan Syarif Kasim State Islamic University, Riau. The study used an ex post facto method with a quantitative approach, involving 50 students as respondents from the classes of 2022, 2023, and 2024. Data were collected through a learning environment questionnaire and a web-based learning style test, then analyzed using normality, homogeneity, multicollinearity tests, as well as t-tests, F-tests, and multiple linear regressions. The results of the study showed that both the learning environment and learning style partially and simultaneously had a significant effect on student learning outcomes, with a significance value of p <0.05 in all tests conducted. A conducive learning environment and adjustment of learning styles according to individual characteristics have been shown to increase students' motivation, understanding, and academic achievement. These findings emphasize the importance of efforts to improve the quality of the learning environment and understanding of learning styles in supporting academic success in the field of mathematics education.